Patient-related constraints on get- and be-passive uses in English: evidence from paraphrasing - Thompson, Dominic; Ling, Shuping; Myachykov, Andriy; Ferreira, Fernanda; Scheepers, Christoph (Frontiers in Psychology, 2013)
In English, transitive events can be described in various ways. The main possibilities are active-voice and passive-voice, which are assumed to have distinct semantic and pragmatic functions. Within the passive, there are two further options, namely be-passive or get-passive. While these two forms are generally understood to differ, there is little agreement on precisely how and why. The passive Patient is frequently cited as playing a role, though again agreement on the specifics is rare. Here we present three paraphrasing experiments investigating Patient-related constraints on the selection of active versus passive voice, and be- versus get-passive, respectively. Participants either had to re-tell short stories in their own words (Experiments 1 and 2) or had to answer specific questions about the Patient in those short stories (Experiment 3). We found that a given Agent in a story promotes the use of active-voice, while a given Patient promotes be-passives specifically. Meanwhile, get-passive use increases when the Patient is marked as important. We argue that the three forms of transitive description are functionally and semantically distinct, and can be arranged along two dimensions: Patient Prominence and Patient Importance. We claim that active-voice has a near-complementary relationship with the be-passive, driven by which protagonist is given. Since both get and be are passive, they share the features of a Patient-subject and an optional Agent by-phrase; however, get specifically responds to a Patient being marked as important. Each of these descriptions has its own set of features that differentiate it from the others.